Combined therapy of acute respiratory viral infections, including coronavirus infection, using a specialized mattress in the background - Kryzhanovskii, Edvard V.; Yavorsky, Alexander B. (International Journal of Research in Medical Sciences, 2020)
Background: Acute respiratory viruses are associated with lower respiratory tract diseases, providing an essential load on the public health system worldwide. Acute respiratory tract infections can be caused by many different viruses, and no approved vaccines or medicines exist for most of them. New approaches to respiratory infection treatment complement the molecular methods by focusing on improving the quality of daily life stages. One of the most important stages is sleep, which is associated with the overall organism restoration and, therefore, is critical to the recovery efficacy. We consider a specialized mattress with a bioactive vicuna cover as a facility improving the sleep quality and estimate its influence on the respiratory infection dynamics for patients under treatment by conventional medication. Methods: Data from 24 patients with the acute respiratory viral infection were collected in the 5 day period, during which they were treated with conventional medication and were sleeping either on the specialized mattresses or on regular mattresses. The patients were split into four groups depending on the mattress type and information that they had about that type, under the double-blind experiment setup. The data comprised the dynamics of several symptoms of the disease, including fever, headache, cough, mucosal hyperemia, and others. Results: Patients with the acute respiratory viral infection demonstrated faster recovery under conditions of sleeping on the specialized mattresses, as compared to the patients who were sleeping on regular mattresses. This difference in the recovery rate was observed for all considered symptoms of the disease, with the largest difference exhibited by nasal congestion (33% difference in the rate between the specialized and regular mattress groups), cough (25%), and rheum (25%). The control for the placebo effect did not reveal its essential influence for most symptoms. Conclusions: The specialized mattresses with the bioactive vicuna cover can effectively be used by patients with the acute respiratory viral infection in addition to conventional tools and medicine. Sleeping on these mattresses alleviate the dynamical state of patients with the disease and facilitates in relieving patients of the symptoms.